2007
DOI: 10.1111/j.1365-2826.2007.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotrophin‐Releasing Hormone, Vasoactive Intestinal Peptide, Prolactin‐Releasing Peptide and Dopamine Regulation of Prolactin Secretion By Different Lactotroph Morphological Subtypes in the Rat

Abstract: In the male rat anterior pituitary, three morphological subtypes of cells secreting primarily prolactin (PRL) (lactotrophs) have been described. Type I contain predominantly large irregularly shaped granules, whereas type II and type III lactotrophs contain smaller spherical granules. We have previously shown that oestradiol and testosterone exert a rapid stimulatory effect selectively on type II lactotrophs but it is not known how the lactotroph subtypes respond to peptide secretagogues. We have therefore exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…In rats the PrRPs-31 stimulates exocytosis of prolactin selectively from type II and type III lactotrophs but not from type I PRL-producing cells (Christian et al, 2007). These results indicate that respective receptors and signalling cascades required inducing PRL release.…”
Section: Factors Stimulating Prolactin Releasementioning
confidence: 52%
See 4 more Smart Citations
“…In rats the PrRPs-31 stimulates exocytosis of prolactin selectively from type II and type III lactotrophs but not from type I PRL-producing cells (Christian et al, 2007). These results indicate that respective receptors and signalling cascades required inducing PRL release.…”
Section: Factors Stimulating Prolactin Releasementioning
confidence: 52%
“…TRH receptors have been identified on type II and type III of lactotrophs but not any labelling was evident on type I. Other studies have revealed that the stimulatory influence of PrRPs-31 on PRL release in rats is rather low compared to TRH or VIP (Samson et al, 1998;Curlewis et al, 2002;Swinnen et al, 2005;Christian et al, 2007).…”
Section: Factors Stimulating Prolactin Releasementioning
confidence: 88%
See 3 more Smart Citations